PENERAPAN MODEL PROBLEM BASED LEARNING DENGAN MENGGUNAKAN PENDEKATAN SAINTIFIK - Achmad, Harmitha (Indonesian Journal of Educational Technology, 2023)
This study examines the application of the problem-based learning (PBM) model with a scientific approach to learning mathematics in high school. The results showed that PBM with a scientific approach was effective in improving learning outcomes and student activeness compared to conventional methods. Specifically, this study found an increase in student learning outcomes from cycle 1 to cycle 2 after implementing PBM with a scientific approach. In addition, student activeness during learning also increased significantly. There is a very strong correlation between student engagement and learning outcomes. PBM encourages active learning and develops critical thinking, problem solving, communication, and 21st-century skills relevant to mathematics and real-world applications. The scientific approach provides a systematic process for scientific thinking and inquiry, enhancing meaningful learning. In conclusion, PBM with a scientific approach is an effective learning strategy in high school mathematics education.